The impact of multidisciplinary team meetings on patient assessment, management and outcomes in oncology settings: A systematic review of the literature. (January 2016) - Pillay, Brindha; Wootten, Addie C.; Crowe, Helen; Corcoran, Niall; Tran, Ben; Bowden, Patrick; Crowe, Jane; Costello, Anthony J.
Highlights: A systematic review of the empirical benefits of MDT meetings was conducted. MDT meetings had a limited impact on patient survival outcomes. Patients discussed were more likely to receive complete pre-operative staging. Patients discussed were more likely to receive neo-adjuvant/adjuvant treatment. 4–50% of patients experienced changes in diagnostic reports following MDT meetings. Abstract: Background: Conducting regular multidisciplinary team (MDT) meetings requires significant investment of time and finances. It is thus important to assess the empirical benefits of such practice. A systematic review was conducted to evaluate the literature regarding the impact of MDT meetings on patient assessment, management and outcomes in oncology settings. Methods: Relevant studies were identified by searching OVID MEDLINE, PsycINFO, and EMBASE databases from 1995 to April 2015, using the keywords: multidisciplinary team meeting * OR multidisciplinary discussion * OR multidisciplinary conference * OR case review meeting * OR multidisciplinary care forum * OR multidisciplinary tumour board * OR case conference * OR case discussion * AND oncology OR cancer . Studies were included if they assessed measurable outcomes, and used a comparison group and/or a pre- and post-test design. Results: Twenty-seven articles met inclusion criteria. There was limited evidence for improved survival outcomes of patients discussed at MDT meetings. Between 4% and 45% of patients discussed at MDT meetings experienced changes in diagnostic reports following the meeting. Patients discussed at MDT meetings were more likely to receive more accurate and complete pre-operative staging, and neo-adjuvant/adjuvant treatment. Quality of studies was affected by selection bias and the use of historical cohorts impacted study quality. Conclusions: MDT meetings impact upon patient assessment and management practices. However, there was little evidence indicating that MDT meetings resulted in improvements in clinical outcomes. Future research should assess the impact of MDT meetings on patient satisfaction and quality of life, as well as, rates of cross-referral between disciplines.